2007
DOI: 10.1111/j.1541-4337.2007.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in the Development and Application of Edible Coatings for Fresh and Minimally Processed Fruits and Vegetables

Abstract: One of the major growth segments in the food retail industry is fresh and minimally processed fruits and vegetables. This new market trend has thus increased the demands to the food industry for seeking new strategies to increase storability and shelf life and to enhance microbial safety of fresh produce. The technology of edible coatings has been considered as one of the potential approaches for meeting this demand. Edible coatings from renewable sources, including lipids, polysaccharides, and proteins, can f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
301
2
24

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 521 publications
(360 citation statements)
references
References 169 publications
(70 reference statements)
3
301
2
24
Order By: Relevance
“…Mint oil coating significantly delayed the drop in fleshfirmness during the storage of guava fruits and retained maximum texture (67%) up to 9 days of storage, the corresponding results for UVC treated lots and the untreated control were 11% and 4%, respectively (Table 6). The edible oil coatings preserve the quality of fruits, retard ethylene emission and enhance texture (Lin and Zhao, 2007). These results validate the findings of Dashora etal.…”
Section: Effect On Flesh Firmnesssupporting
confidence: 81%
“…Mint oil coating significantly delayed the drop in fleshfirmness during the storage of guava fruits and retained maximum texture (67%) up to 9 days of storage, the corresponding results for UVC treated lots and the untreated control were 11% and 4%, respectively (Table 6). The edible oil coatings preserve the quality of fruits, retard ethylene emission and enhance texture (Lin and Zhao, 2007). These results validate the findings of Dashora etal.…”
Section: Effect On Flesh Firmnesssupporting
confidence: 81%
“…Thus, coating reduces the enzyme activity. Lin and Zhao (2007) also reported that the coating provides sufficient gas barrier for controlling gas exchange between the fresh produce and its surrounding atmosphere, which would slow down respiration and delay deterioration. The gas-barrier function could in turn retard the enzymatic oxidation and protect the fresh produce from browning discoloration and texture softening during storage.…”
Section: Effect On Softening Related Enzymesmentioning
confidence: 99%
“…One such polymer is carboxymethyl cellulose (CMC), which can be prepared in the form of an aqueous "gel-like" viscous solution with characteristics similar to a biological cell. CMC has been used in various practical fields [7,8,9]. In one such application [10], He Huang et al studied electrochemical properties of proteins or enzymes such as Heme protein at CMC modified electrodes.…”
Section: Introductionmentioning
confidence: 99%